Automatic Door for Cat with Air Freshener Sprayer - AZMAN, NURHANIS ATIQAH; ZOHARI, MOHD HAKIMI (Progress in Engineering Application and Technology, 2023)
The project proposes an automatic and precise door opening system based on cat movement sensing near the door, which is provided by an infrared and ultrasonic sensor. The system also includes an intelligent air freshener with an automatic door, which includes a user-operated remote controller that detects the signal via an infrared or ultrasonic sensor. This study aims to develop a motion detection sensor capable of opening and closing doors, monitoring objects, displaying results on LCD. To ensure safety, it will be equipped with ultrasonic sensors to sense any obstructions that are in its way. Lastly, the air fragrance with the use of sensor and Blynk Application is proposed for the system.